2018
DOI: 10.1002/er.4040
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Ni3Sn4-based graphene@carbon hybrid composites for lithium-ion batteries

Abstract: Summary In this paper, nanosized Ni3Sn4 nanoparticles were synthesized by chemical reduction technique. A facile strategy is also developed to synthesize the yolk‐shell Ni3Sn4 nanoparticles decorated between the layers of multilayer graphene to obtain high‐capacity, long service life with comparable cost Li‐ion batteries. Ni3Sn4 nanoparticles in the form of yolk‐shell morphology were synthesized between 30 and 130 nm in size and homogeneously anchored on graphene layers as spacers preventing the layers merging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Thus, the electrochemical reaction of Li with the prepared ZMO500 sample was investigated by cyclic voltammetry (CV) and galvanostatic cycling. Furthermore, the ZMO500 composite electrode (ZMO‐G500), prepared by the incorporation of graphene nanosheets (GNS), exhibited enhanced reversible capacity and cycle retention as a result of its more efficient electron transport paths and stress relaxation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the electrochemical reaction of Li with the prepared ZMO500 sample was investigated by cyclic voltammetry (CV) and galvanostatic cycling. Furthermore, the ZMO500 composite electrode (ZMO‐G500), prepared by the incorporation of graphene nanosheets (GNS), exhibited enhanced reversible capacity and cycle retention as a result of its more efficient electron transport paths and stress relaxation …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ZMO500 composite electrode (ZMO-G500), prepared by the incorporation of graphene nanosheets (GNS), exhibited enhanced reversible capacity and cycle retention as a result of its more efficient electron transport paths and stress relaxation. 42,43 2 | EXPERIMENTAL PROCEDURES…”
mentioning
confidence: 99%
“…Batteries have been broadly applied for communication devices and new energy vehicles because of the environmental friendliness and high energy density . For lithium ion batteries (LIBs), the tremendous demand for lithium results in its unavailability . Thus, exploring affordable and sustainable energy storage devices is extremely important.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding performance of SnO 2 electron transport layers is attributed to the excellent properties of nanocrystalline SnO 2 films, such as good reflection, suitable band edge position, and high electron mobility. The SnO 2 electron selective layer-based perovskite solar cells showed higher short-circuit current density and lower open-circuit voltage, fill factor, and conversion efficiency than the conventional TiO 2 electron selective layer-based perovskite solar cells as demonstrated by Qingshun et al 12 Similarly, many researchers reported different methods for preparation of SnO 2 nanosheets 20 and ZnO-SnO 2 nanocomposites 21 for application in perovskite solar cells whereas SnO 2 /graphene composite 22 for lithium-ion batteries 23 and different graphene-based electrodes for dye-sensitized solar cells. 16,[24][25][26] Inthepresentexperimentalwork,transparentelectrodes based on SnO 2 -graphene with different compositions have been prepared through redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many researchers reported different methods for preparation of SnO 2 nanosheets and ZnO‐SnO 2 nanocomposites for application in perovskite solar cells whereas SnO 2 /graphene composite for lithium‐ion batteries and different graphene‐based electrodes for dye‐sensitized solar cells …”
Section: Introductionmentioning
confidence: 99%